Get detailed and accurate responses to your questions with IDNLearn.com. Our platform provides detailed and accurate responses from experts, helping you navigate any topic with confidence.

In the quadratic equation, 6x^2-gx+2=0 , the sum of the roots is equal to three times their product

Sagot :

Answer:

g = 6

Step-by-step explanation:

To find the value of g in quadratic equation 6x² - gx + 2 = 0, we can use Vieta's formulas.

[tex]\boxed{\begin{array}{l}\underline{\textsf{Vieta's Formulas for Quadratic Equation}}\\\\\textsf{If $f(x) = ax^2+ bx + c$ has roots $\alpha$ and $\beta$ then:}\\\\\textsf{Sum of the roots:}\quad \alpha+\beta=-\dfrac{b}{a}\\\\\textsf{Product of the roots}\quad \alpha\cdot\beta=\dfrac{c}{a}\end{array}}[/tex]

Given that the sum of the roots is equal to three times their product:

[tex]-\dfrac{b}{a}=3\cdot \dfrac{c}{a}[/tex]

In this case:

  • a = 6
  • b = -g
  • c = 2

Substitute these values into the equation:

[tex]-\dfrac{-g}{6}=3\cdot \dfrac{2}{6}[/tex]

Now, solve for g:

[tex]\dfrac{g}{6}=3\cdot \dfrac{2}{6}\\\\\\\dfrac{g}{6}=\dfrac{6}{6}\\\\\\\dfrac{g}{6}=1\\\\\\g=6[/tex]

Therefore, the value of g is:

[tex]\LARGE\boxed{\boxed{g=6}}[/tex]